Analisis Risiko Pada Usahatani Kubis Di Desa Dukuhdempok Kecamatan Wuluhan Kabupaten Jember - Prisya Niken Mahardika Putri; Anik Suwandari (UPT Penerbitan Universitas Jember, 2018)
Cabbage is one of Dukuhdempok’s superior commodities. The drastic decline of cabbageproduction in 2017 showed a production risk on cabbage farming. In addition, the selling systemby bought before harvesting showed that farmers only act as price taker and it indicated the pricerisk. Based on that, this research is conducted to know: (1) The level of production risk and pricerisk on cabbage farming, and (2) Farmer’s behavior in facing the price risk of cabbage farming. Themethod of determining research area is done using purposive method, there was DukuhdempokDukuhdempok Village Wuluhan Sub-district Jember Regency as research area. The researchmethod used descriptive and analytical method. The sampling method used purposive and totalsampling. The samples are cabbage farmer of ―Rukun Tani‖ group amount 33 farmer. Datacollection method is done by obeservation, interview, and documentary study. Data analysismethod of production risk and price risk is done by value of coefficient variation analysis. Farmer’sbehavior in facing the price risk of cabbage farming is analyzed by quadratic utility function thatusing software of SPSS Statistics v23. The results showed that: (1) Production risk level withvalue of CV was 0,44 < 0,5 and price risk with value of CV 0,35 < 0,5 so both of them were lowlevel. (2) Mostly 78,8% or 26 persons of cabbage farmers were risk neutral; 15,2% or 5 personwere risk averter; and 6,1% or 2 person were risk taker